Response of Melia dubia and Dalbergia sissoo to Sandy Loam Soil Amended with Water Absorbent Polymer in Establishment Phase - Dhakad, Ashok Kumar; Kumar, Rajesh; Singh, Avtar; Kaur, Nirmaljit (Indian Forester, 2025)
The present study aimed to assess the effect of water absorbent polymers application on the survival, growth performance, biomass and leaf physiological characteristics of short rotation i.e., Melia dubia and long rotation tree species i.e., Dalbergia sissoo. The hydrogel was applied in powdered form before planting the seedlings in soil pits of 50×50×50 cm3 volume at concentrations of, 0, 25, 30, 35, 40, 45 and 50 g/pit. A significant increase was recorded with increasing the amount of hydrogel for both species. In M. dubia, treatment T2 (30 gm/pit) was found best for growth and biomass parameters and lowest was in control. The nitrogen (N), potassium (K) and physiological parameters such as relative water content (RWC) and membrane stability index (MSI) were also recorded higher in T2 (30 gm/pit), while phosphorous (P) was in T3 (35 gm/pit) treatment. Total carotenoid was recorded maximum for both T2 (30 gm/pit) and T3 (35 gm/pit). Chlorophyll content increased with increasing dose of hydrogel application and the maximum was in T6 (50 gm/pit), while TSS showed a reverse pattern and the maximum was in T1 (25 gm/pit). In case of long rotation tree species i.e. D. sissoo, growth and biomass was in general higher in treatment T3 (35 gm/pit) and minimum in control.